Analysis and Mechanism of Settlement of Insurance Claims of PT Prudential Syariah Prestasi Binjai - Regi Utami Nasution; Tri Inda Fadhila Rahma (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
From the data, Indonesia is a country that is generically controlled by a Muslim population. And Prudential Insurance is an opportunity to meet the needs of Muslims using premiums according to sharia. Therefore, prudential companies provide various insurance premiums such as life insurance and asset management. The Prudential Syariah Prestasi Binjai Insurance company not only offers the products that have been described but also helps provide protection for the insured along with investing in a very long period of time and has a high risk. The purpose of this study is to increase knowledge on the procedure for the claim settlement mechanism at PT Prudential Syariah Prestasi Binjai. This study uses qualitative data collection techniques using literature studies and interviews based on several company sources at PT Prudential Syariah Prestasi Binjai. And the output based on this research tells that the benefits of PT Prudential Syariah put 99 (ninety nine) years of protection combined using investment. Meanwhile, the prudential insurance claim mechanism will go through a process that has been determined in the policy and the claim section has been prepared, where the insured is required to fill out all the specified claim forms.